(untitled) - Kimball, Dan A. (Gaithersburg, Md., 1999)
Provides an introduction to citrus processing followed by a review of business fundamentals applied to the citrus processing industry. This title covers: the integration of computer communications, descriptions of equipment and engineering needed to put a plant together, quality control, and procedures and ramifications of juice characteristics.
Keywords: Citrus juices,Citrus products,Nước trái cây họ cam quýt